The correlation between birth weight and insulin-like growth factor-binding protein-1 (IGFBP-1), kisspeptin-1 (KISS-1), and three-dimensional fetal volume. (3rd July 2019) - Kimyon Comert, Gunsu; Esin, Sertac; Caglar, Gamze Sinem; Yirci, Bulent; Ozdemir, Sedat; Demirtas, Selda; Kandemir, Omer
Abstract: Purpose: This study aimed to determine the relationship between birth weight, and maternal serum insulin-like growth factor-binding protein-1 (IGFBP-1) and kisspeptin-1 (KISS-1) levels, and first-trimester fetal volume (FV) based on three-dimensional ultrasonography. Materials and methods: The study included 142 pregnant women at gestational week 11°–13 6 . All fetuses were imaged ultrasonographically by the same physician. Maternal blood samples were collected at the time of ultrasonographic evaluation and analyzed for IGFBP-1 and KISS-1 levels via enzyme-linked immunosorbent assay (ELISA). Maternal and neonatal weights were recorded at birth. Birth weight ≤10th and the >90th percentiles was defined as small and large for gestational age (SGA and LGA), respectively. Results: Median crown-rump length (CRL), FV, and maternal serum IGFBP-1 and KISS-1 levels were 58.2 mm (35.3–79.2 mm), 16.3 cm 3 (3.8–34.4 cm 3 ), 68.1 ng mL −1 (3.8–377.9 mL −1 ), and 99.7 ng L −1 (42.1–965.3 ng L −1 ), respectively. First-trimester IGFBP-1 levels were significantly lower in the mothers with LGA neonates ( p < .05). There was a significant positive correlation between CRL and FV, and between the IGFBP-1 and KISS-1 levels. IGFBP-1 levels and maternal weight at delivery were negatively correlated with neonatal birth weight. There was no correlation between CRL or FV and maternal IGFBP-1 or KISS1 levels ( p > .05). The maternal IGFBP-1 level during the first trimester was a significant independent factor for SGA and LGA neonates (Odds ratio (OR): 0.011, 95%CI: 1.005–1.018, p < .001; and OR: 1.297, 95%CI: 1.074–1.566, p = .007, respectively). There was no significant relationship between SGA or LGA, and CRL, FV, or the KISS-1 level. Conclusions: As compared to the maternal KISS-1 level, the maternal IGFBP-1 level during the first trimester might be a better biomarker of fetal growth. Additional larger scale studies are needed to further delineate the utility of IGFBP-1 as a marker of abnormal birth weight.